Analysis of Process of Plate Piercing by Small Dimension Cylindrical Element - Robert PANOWICZ; Damian KOŁODZIEJCZYK; Kamil SYBILSKI; Tadeusz NIEZGODA (Problemy Mechatroniki, 2014)
The article presents an initial verification of interaction of a small dimension cylindrical element with an obstacle in the form of a 2.5 mm thick metal shield. There were considered impacts at different velocities (200 , 400 and 800 m/s) and different impact angles (30, 45, 60 and 90°) for two different types of materials: aluminium alloy PA7 and copper tape. Based on these results, there was determined the area of changes which were formed in the material as a result of the impact. A three-dimensional numerical model was developed in HyperMesh system [1] and analyses of high-frequency phenomena were performed with the use of a nonlinear finite element method included in LD-Dyna software [2]. Implementation of numerical analyses would enable the investigation of the considered in the present work dynamic phenomena impossible to be recorded with experimental methods. Application of LS-Dyna enabled both the investigation of damages propagation in the subsequent time steps and stress distribution in the material. The tests carried out in the present work allowed more accurate knowledge of physics of a piercing process phenomenon.